Dielectric relaxations in Ho2Ti2O7 and Dy2Ti2O7 pyrochlores. (November 2019) - Yadav, Pramod K.; Tolkiehn, Martin; Upadhyay, Chandan
Abstract: Dielectric measurements of Ho2 Ti2 O7 and Dy2 Ti2 O7 cubic pyrochlore show two distinctly defined relaxations around 90K and 36K. The nature and possible origin of these relaxations have been determined. The observed value of critical exponent of Curie-Weiss and Lacroix- B e ′ n e ′ equation confirms these relaxations are diffuse and show Debye-like behavior. The order of activation energy of Ho2 Ti2 O7 and Dy2 Ti2 O7 shows that both relaxations are distinctly related with structural distortion at oxygen sites. Temperature-dependent lattice volume shows deviation from Debye-Grüneisen behavior below 70 K, further confirms the structural origin of both relaxations. An underlying crystal field anisotropy induced splitting of multipolar order parameter is the primary cause of both diffuse relaxations in these spin ices. It has been found that dielectric relaxations depend strongly on the crystal field, which provides a tool to fine tune the dielectric properties of these systems. Highlights: Detailed study of dielectric responses of Ho2 Ti2 O7 and Dy2 Ti2 O7 spin ice pyrochlores. Low temperature synchrotron x-ray diffraction to confirm the crystallographic stability. Role of single ion anisotropy and a non-Ising to Ising spin crossover in dielectric response of Ho2 Ti2 O7 and Dy2 Ti2 O7 . Curie-Weiss and Lacroix- B e ′ n e ′ analysis confirms the nature of dielectric relaxations as diffusive relaxation.